As estratégias discursivas e suas implicações na relação entre oralidade e escrita? um estudo do parêntese na crônica - Neves, Maria Helena de Moura [UNESP] (My University, 2012)
Based on functional theory, the text discusses the relations between spoken language and written language, defending not only the existence of a sole grammatical system for both, but also the relevance of studies contemplating specificities of use, some of these being more directed toward interaction, and others being more directed toward system. The investigation that aims to prove these premises used the chronicle as examination material, due to its linguistic colloquialism in general and due to the chronicler’s personal engagement, which involve linguistic strategies available for the expression of information and for the reader’s understanding. The investigation was concentrated on the discourse parenthesis, especially on its connection with the degree of language planning and with the creation of view plans and the establishment of emphasis. It was concluded that the resource of parenthesis both represents linguistic informality (which is more directed toward speaking) and shows the care with preparation and marking of style (which is more directed toward writing), illustrating specificities.

Com aparato funcionalista o texto discute as relações entre língua falada e língua escrita, defendendo a existência de um sistema gramatical único para ambas, mas também a pertinência de estudos que contemplem as especificidades de uso, algumas delas mais na interação, outras, mais no sistema. A investigação que busca comprovar essas premissas teve como material de exame a crônica, dada a coloquialidade de sua linguagem no geral e dado o engajamento pessoal do cronista, o que envolve estratégias linguísticas disponíveis para explicitação da informação e para captação do leitor. Ela se concentrou no parêntese discursivo, especificamente em sua ligação com o grau de planejamento da linguagem e com a criação de planos de visão e o estabelecimento de relevos. Concluiu-se que o recurso ao parêntese tanto representa informalidade de linguagem (mais para a fala) como evidencia cuidado de elaboração e marcação de estilo (mais para a escrita), ilustrando especificidades.
Keywords: Speaking and writing; Discourse strategies; Functionality; Parenthesis; Chronicle; Fala e escrita; Estratégias discursivas; Funcionalismo; Parêntese; Crônica